2021
DOI: 10.1021/acs.macromol.0c02405
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and Substrate Dependences of the Relaxation of Spin-Coated Polymethyl Methacrylate Ultrathin Films Supported on SiO2 and SiOH Substrates

Abstract: The relaxation of ultrathin polymethyl methacrylate (PMMA) films, which were spin-coated on SiO2 and SiOH substrates, was examined with different film thicknesses. In the glassy state, several relaxation processes revealed temporal variations in thicknesses. In sharp contrast to bulk PMMA in which the monotonic volume reduction was expected, the ultrathin films exhibited thickness variations, which would be classified into at least four types: (1) a slow increase in the thickness with time, where the thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…Based on the results provided in this study, as well as the results of PS and PMMA from previous studies, , it can be suggested that at least two competing relaxation processes are taking place in ultrathin glassy polymers. One dominates in the glassy state, giving rise to NTE, while the other takes over in the melt state, resulting in thickness contraction even at temperatures higher than T g bulk .…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Based on the results provided in this study, as well as the results of PS and PMMA from previous studies, , it can be suggested that at least two competing relaxation processes are taking place in ultrathin glassy polymers. One dominates in the glassy state, giving rise to NTE, while the other takes over in the melt state, resulting in thickness contraction even at temperatures higher than T g bulk .…”
Section: Resultssupporting
confidence: 71%
“…Such an intriguing and unusual behavior of thickness expansion in the glassy state and shrinkage in the melt state were also seen in well-annealed PS films supported on SiO 2 and PMMA on SiO 2 and SiOH substrates in our previous studies. 41,42 Thickness expansion in PMMA was observed for films with thickness less than their R g values; above R g , data showed a competing behavior between thickness expansion and contraction, and finally for the thickness greater than 2.5R g or 3R g , the thickness decreased with time. In contrast to PMMA films, 41 which experienced thickness expansion for films with an initial thickness of < R g , PVPh films exhibited thickness expansion for all of the films ranging from 30 Å (∼0.75R g ) to 140 Å (∼3.5R g ).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 3 more Smart Citations